DESIGN OF PERMANENT MAGNET LINEAR SYNCHRONOUS MOTOR DRIVING 2D TABLE FOR LASER MARKING (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In this paper, the results from design of a permanent magnet linear synchronous motor are published. The motor will drive a table for laser marking of various small details. This table will be part of the equipment of Laser Technologies Laboratory of the Research Centre for Physical Processes and Laser Technologies at Rezekne Academy of Technologies. In the design process, a comprehensive approach was used in which the theory of electric and magnetic circuits was combined with Finite Element Method (FEM). The paper contains the main equations of the design methodology. They were used for the preliminary calculation of motor magnetic system and main electromagnetic parameters via script program. For the specifying of these quantities and motor optimization, the results from modeling and analyzing of the linear motor magnetic field by the FEM were used.